The Effect of Entrepreneurial Orientation on Native Chicken Farm Growth With The Mediating Role of Poultry Production Systems - Mappigau, Palmarudi; Upe, Jusni Ambo (Indonesian Journal of Business and Entrepreneurship, 2022)
Growth among native chickens farming is eminent to accelerate the rate of poverty reduction and improve food security and nutrition by increasing the consumption of meat and eggs as a source of high-quality protein. Furthermore, entrepreneurial orientation (EO) has been widely used as a strategic approach for enhancing farm growth through various innovations. Therefore, this study aims to determine the effect of EO and poultry production systems on the growth of native chickens and to find out how the mediating role of poultry production systems on the effect of EO on the growth of native chicken farms. This study used a quantitative study focused on direct observation and structured interviews. A probability with a simple random sampling procedure was used for collecting the data from 196 native chicken farmers across Bone Regency, South Sulawesi Province, through a questionnaire. The data obtained were analyzed using path analysis. The results showed that EO and poultry production systems positively and significantly affected native chicken farm growth. However, the contribution of the effect of EO on the native chicken farm growth was lower (5.77%). After adopting the model's poultry production systems as a moderating variable, the effect's contribution increased to 16.57%. Based on the study findings, the study concluded that the adopted poultry production systems practices serve as a moderating variable that contributes mainly to the effect of EO on native chicken farm growth. Keywords: entrepreneurial orientation, poultry production system, native chicken, farm growth, mediating variable